2015
DOI: 10.1037/a0038034
|View full text |Cite
|
Sign up to set email alerts
|

Excluded and behaving unethically: Social exclusion, physiological responses, and unethical behavior.

Abstract: Across 2 studies, we investigated the ethical consequences of physiological responses to social exclusion. In Study 1, participants who were socially excluded were more likely to engage in unethical behavior to make money and the level of physiological arousal experienced during exclusion--measured using galvanic skin response--mediated the effects of exclusion on unethical behavior. Likewise, in Study 2, results from a sample of supervisor-subordinate dyads revealed a positive relationship between experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…In particular, previous studies have found that ostracism can lead to an array of undesirable effects that potentially violate social rules. For instance, ostracized people are more likely to behave dishonestly than non-ostracized people (Kouchaki & Wareham, 2015;Poon et al, 2013) and engage in risk-taking behavior (Duclos et al, 2013;Twenge, Catanese, & Baumeister, 2002). We suggest that enhanced feelings of rule negligence may be able to account for these POON AND TENG | 565 influences of ostracism, and that manipulating ostracized people to perceive the importance in following rules can reduce these impacts.…”
Section: Limitations and Future Directionsmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, previous studies have found that ostracism can lead to an array of undesirable effects that potentially violate social rules. For instance, ostracized people are more likely to behave dishonestly than non-ostracized people (Kouchaki & Wareham, 2015;Poon et al, 2013) and engage in risk-taking behavior (Duclos et al, 2013;Twenge, Catanese, & Baumeister, 2002). We suggest that enhanced feelings of rule negligence may be able to account for these POON AND TENG | 565 influences of ostracism, and that manipulating ostracized people to perceive the importance in following rules can reduce these impacts.…”
Section: Limitations and Future Directionsmentioning
confidence: 87%
“…For instance, ostracized people are more likely to behave dishonestly than non-ostracized people (Kouchaki & Wareham, 2015;Poon et al, 2013) and engage in risk-taking behavior (Duclos et al, 2013;Twenge, Catanese, & Baumeister, 2002). It is still unsure whether rule negligence carries implications in understanding other impacts of ostracism.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Moreover, our use of experimental methods represents a further contribution. Although prior research has examined work behavior as an outcome of social rejection, only a handful of studies have relied on experimental designs (e.g., Kouchaki & Wareham, 2015;Thau, Derfler-Rozin, Pitesa, Mitchell, & Pillutla, 2015) to ensure the detection of causal relationships between variables (Aronson, Carlsmith, & Ellsworth, 1990). Our experimental results extend the literature on social rejection by providing causal evidence for the impact of social rejection on a work outcome (employee voice).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Although the concept of exclusion has been explored many times in the field of social psychology, the exclusion in the work environment has only examined in the recent studies (Ferris, Brown, Berry, & Lian, 2008, Robinson et al, 2013Kouchaki & Wareham, 2015). The exclusion is a major obstacle for establishing and maintaining relationships among people, therefore its impact is significantly important for employees and the organizations.…”
Section: Organizational Exclusionmentioning
confidence: 99%